P442 Implementing pre-exposure prophylaxis for HIV: experiences in a health department based STI clinic. (14th July 2019) - Lewis, Andrea; Mcneil, Candice; Hicks, Karen; Russell, Gregory
Abstract : Background: Despite the availability of PrEP, the uptake is suboptimal. Guilford County in North Carolina has seen a steady increase in the rates of HIV amongst high-risk groups, especially Black men-who-have-sex-with men (MSM). Many people receive preventative services through health departments and they are expected to play an integral role in PrEP services. The Guilford County Health Department (GCHD) PrEP clinic was established to provide services to their patients who were at high-risk of acquiring HIV. The aim of this study is to describe a health department's experience in implementing PrEP services and to identify risk related trends for patients screen/enrolled in an effort to optimize services. Methods: We conducted a retrospective review of six months of data from the GCHD PrEP clinic. Fisher's Exact Tests were used to test for differences between groups for outcomes of interest. Results: Between March 2018 and September 2018, 65 patients were referred to the PrEP clinic for initiation of PrEP. 94% of all patients were male. Forty-eight patients identified as MSM of which 63% were Black. Of all patients screened at their referral visit for STIs, over half (55%) tested positive for at least one bacterial STI, with pharyngeal gonorrhea being the most common (p=0.022). Forty-six patients were prescribed PrEP, 31 were insured. 3 HIV seroconversions occurred in the interval between referral and initial PrEP visit. Conclusion: Majority of new HIV cases in Guilford County occur in Black MSM, and most of the patients screened for PrEP services at the clinic were Black MSM indicating that the patients accessing PrEP services are those that are most greatly impacted by the HIV epidemic in Guilford County. The high prevalence of STIs among patients initiating PrEP emphasizes the opportunity and significance of simultaneous STD screening and PrEP services. Financial resources have helped offer PrEP to high-risk groups. Disclosure: No significant relationships.